Парик для дамы пик: [роман] / А. В. Данилова - Данилова Анна Васильевна (Леди-детектив, 2005)
Экземпляры: аб. (2006) / Инвентарный номер: 49713 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Д 18 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44